Model MSDM Berbasis Nilai: Internalisasi Etika Pesantren dalam Mengatasi Krisis Integritas Tenaga Kerja Modern - M. Ilham Faizin Akbar; Siti Aimiah (Lembaga Yasin AlSys, 2026)
The integrity crisis in the modern workforce constitutes a critical challenge in Human Resource Management (HRM) and requires a developmental approach oriented not only toward technical competence but also toward strengthening the moral dimension. This study aimed to analyze the impact of pesantren values on optimizing community HRM quality and to formulate a value-based HRM model relevant to the needs of the contemporary workplace. The study employed a qualitative case study with a phenomenological approach, in which data were obtained through interviews and observations and then analyzed through a systematic data-reduction process. The findings showed that the internalization of istiqomah, riyadhah, and kemandirian within the pesantren environment transformed individual character and was positively correlated with levels of discipline and loyalty at work. The researcher identified a “Value-Based HRM” model that synergizes technical competence with professional ethics, positioning the pesantren as a strategic incubator for forming human resources with integrity. This study underscores that integrating a value-based model into formal HRM policies is crucial for addressing problems of morality and productivity in both the public and private sectors, while strengthening the ethical foundation of HRM governance in the long term.